Genetic Loci Associated With Periodontitis: The FinnGen Study Based on National Health Registers - Salminen, Aino; Hyvärinen, Kati; Ritari, Jarmo; Caetano, Ana; Kambur, Oleg; Mäntylä, Päivi; Yilmaz, Mustafa; Sinisalo, Juha; FinnGen; Perola, Markus; Havulinna, Aki; Nibali, Luigi; et al. (Wiley-Blackwell, 2026)
Aim
To perform a genome-wide association study (GWAS) for periodontitis in the FinnGen cohort, as genetic factors contribute to periodontitis.
Materials and Methods
We included nearly 250,000 Finnish individuals who had visited a dentist in the public healthcare sector for a clinical oral examination. We designed three periodontitis phenotypes based on diagnosis and procedure codes and CPI indexes in national health registers.
Results
We identified 11 independent genetic loci associated with periodontitis, among which 6 were common and novel. A locus near the FST gene was associated with two phenotypes, whereas other lead SNPs were located near ARL15, MFHAS1, DEFB130A and APOE. Additionally, all phenotypes in the discovery and replication cohorts were associated with genetic variations in the HLA region. Furthermore, imputed HLA allele frequencies identified independent associations between HLA-DRB1, HLA-DPB1 and HLA-DQA1 and periodontitis. Based on single-cell RNA sequencing, the expression of genes near our lead SNPs across all three phenotypes was particularly enriched in gingival cell lineages important in the pathogenesis of periodontitis. Phenotypical and genetic correlations revealed associations between periodontitis and bacterial diseases, as well as autoimmune and cardiometabolic phenotypes.
Conclusions
Our GWAS suggests that genetic variation contributing to immune dysregulation is involved in the pathogenesis of periodontitis, which has considerable genetic similarity with other complex traits.